Effects of Y and Ni co-doping in Bi2Fe4O9 - BiFeO3 based multiferroic ceramics. (2021) - Banerjee, P.; Franco, A.; Xiao, R.Z.
Abstract: Here we reported the structural, microstructural and magnetic properties of BiFeO3 (BFO) and Bi0.99 Y0.01 Fe0.98 Ni0.02 O3 (BYFNO) ceramics modified with mullite type Bi2 Fe4 O9 multiferroic. The XRD results in such unmodified and modified ceramics suggested that the rhombohedral structure was distorted due to the doping where as the modification has an impact on the microstrain parameters. Micro-structural studies clearly showed the growth of average grain size due to the modification in the BFO ceramics. The presence of Bi2 Fe4 O9 on BYFNO ceramic caused an increment in the saturation magnetization up to 0.027 μB /f.u. The origin of such properties has been demonstrated on the basis of size effect, nature of the dopants and modification done in the ceramic systems.